Estimation of the continuity of tillage choices with aggregated and incomplete data: An application of the entropy approach - Tran, Dat Q.; Kurkalova, Lyubov A. (Journal of the Agricultural and Applied Economics Association, 2025)
The environmental benefits of conservation tillage (CT) are fully realized when the practice is used continuously. Little is known about farmer's tillage choice dynamics due to the scarcity of panel tillage data. Using publicly available data, we estimate rotational and continuous CT (CCT) probabilities for 1992–2008 for Iowa, U.S. The results show that approximately one million acres of corn and soybeans moved away from CCT to greater tillage intensity practices in 2001–2008 when corn prices increased sharply. Spatially, more acreage in lower soil productivity and more likely classified as highly erodible land were taken out of CCT during 2001–2008.